Arteriovenous fistulas for microvascular head and neck reconstruction. Issue 3 (August 2015) - Moubayed, Sami P; Giot, Jean-Philippe; Odobescu, Andrei; Guertin, Louis; Harris, Patrick G; Danino, Michel Alain
Background: In head and neck cancer patients, multiple surgeries and radiation can leave the neck depleted of recipient vessels appropriate for microvascular reconstruction. The creation of temporary arteriovenous fistulas using venous interposition for subsequent microvascular reconstruction has rarely been reported in the head and neck. The authors report the largest series of temporary arteriovenous loops for head and neck reconstruction in vessel-depleted necks. Methods: The authors performed a case series of major head and neck reconstructions using temporary arteriovenous fistulas with a saphenous vein graft. A subclavian surgical approach was used. All reconstructions were performed at least two weeks after the creation of the initial fistula. Results: The authors have performed nine reconstructive cases for malignancy using five different free flaps. The subclavian and transerve cervical arteries were used, and the subclavian, internal jugular and cephalic veins were used for microanastomosis. Two cases of flap hematoma and one case of venous pedicle compression were recorded. No cases of flap failure were reported. Conclusions: Reconstruction using temporary arteriovenous fistulas is a reliable technique that can be used in the vessel-depleted neck, with excellent outcomes in experienced hands.